Rapamycin Prevents the Development and Progression of Mutant Epidermal Growth Factor Receptor Lung Tumors with the Acquired Resistance Mutation T790M - Shigeru Kawabata; José R. Mercado-Matos; M. Christine Hollander; Danielle Donahue; Willie Wilson III; Lucia Regales; Mohit Butaney; William Pao; Kwok-Kin Wong; Pasi A. Jänne; Phillip A. Dennis (Cell Reports, 2014)
Lung cancer in never-smokers is an important disease often characterized by mutations in epidermal growth factor receptor (EGFR), yet risk reduction measures and effective chemopreventive strategies have not been established. We identify mammalian target of rapamycin (mTOR) as potentially valuable target for EGFR mutant lung cancer. mTOR is activated in human lung cancers with EGFR mutations, and this increases with acquisition of T790M mutation. In a mouse model of EGFR mutant lung cancer, mTOR activation is an early event. As a single agent, the mTOR inhibitor rapamycin prevents tumor development, prolongs overall survival, and improves outcomes after treatment with an irreversible EGFR tyrosine kinase inhibitor (TKI). These studies support clinical testing of mTOR inhibitors in order to prevent the development and progression of EGFR mutant lung cancers.